The border region of Nunukan Regency with the City of Tawau, Sabah state, Malaysia has great potential to be developed as a center of agricultural production and raw material supplier. The research aims to: (a) Investigating the structure, the actors and - M Abd Nasir; Ciplis Gemah Qori'ah; Yulia Indrawati; Adhitya Wardhono; Satrio Wicaksono (UPT Penerbitan Universitas Jember, 2012)
Government policy on the application of export tax for crude palm oil and its derivatives is preferred to increase government revenue and protection for domestic industry. Potentially, the beneficiary of the application of export taxes is domestic consumer (downstream industry), government and Indonesia's export competitors. Benefit on crude palm oil downstream industries because of the application of the export tax would push the price of crude palm oil and its derivatives in the domestic market. State revenues will increase according with to the tariff, price and export volume. The application of export tax tends to reduce the volume of exports, so that foreign exporters benefit from a reduction in exports of crude palm oil and its derivatives by Indonesia. Meanwhile, the injured parties from the application of export taxes are crude palm oil producers, importers, service providers in the port, input suppliers oil palm estates and state revenue. Export tax would depress prices in domestic market so it results in a disincentive for producer crude palm oil and its derivatives. Based on the above problem, this paper aims to criticize the policy of export tax on crude palm oil industry that has a different impact for consumers, industry, importers, and governments. The second objective to describe by steps to achievement of the implementation of the export tax and the amount of export tax rates to consider benefits for all stakeholders of national oil palm, burden to be borne by stakeholders and the rule of law and its impact on Gross Domestic Product (GDP), the performance of oil palm agribusiness and farmers' income. Problems of implementation of the export tax, the important thing to note is the norm that can be used as a reference in determining the amount of crude palm oil export tax rate and its derivatives. For the determination of the amount of crude palm oil export tax rate should be considering (i) its only charges, not taxes, (ii) a high rate has the potential to destabilize crude palm oil international markets that could pose a negative impact on the crude palm oil domestic market (iii) adjusted by the need for program and activities of development of crude palm oil national industry.